Pengaruh LKPD Terintegrasi Etnis Nusantara terhadap Kemampuan Numerasi Matematis melalui Model Pembelajaran SAVI - Fitry Khairany Pulungan; Yenni Novita Harahap; Yumira Simamora (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the effect of using student worksheets (LKPD) integrated with Nusantara ethnic culture on students’ mathematical numeracy skills through the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model. This research employed a quantitative approach using a true experimental design with a Post-test Only Control Group Design. The participants were eleventh-grade students of SMA Nurul Iman Tanjung Morawa in the 2025/2026 academic year, who were randomly assigned into an experimental class and a control class. The experimental class was taught using culturally integrated LKPD through the SAVI learning model, while the control class received conventional instruction. The research instrument consisted of an essay-type mathematical numeracy test that had been validated by experts. Data were analyzed using normality tests, homogeneity tests, and an independent samples t-test at a 0.05 significance level. The results indicated that the average mathematical numeracy score of students in the experimental class was higher than that of the control class. Hypothesis testing revealed a significance value lower than 0.05, indicating a statistically significant difference between the two groups. These findings demonstrate that the use of LKPD integrated with Nusantara ethnic culture through the SAVI learning model has a positive and significant effect on improving students’ mathematical numeracy skills. Therefore, culturally integrated worksheets can serve as an effective contextual learning alternative to enhance students’ mathematical numeracy abilities.